2023
DOI: 10.3390/ijerph20075413
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a 12-Week-Long Sand Exercise Training Program on Neuromechanical and Functional Parameters in Type II Diabetic Patients with Neuropathy

Abstract: Studies have proven the effectiveness of different weight-bearing exercise interventions for diabetic patients with neuropathy; however, several adverse effects were reported using solid surfaces. Thus, in the present study, we investigated the effects of a novel sand exercise training intervention on biomechanical and functional parameters in seven diabetic patients (age = 62.7 ± 9.7 years) with neuropathy. Patients underwent a 12-week sand exercise training program, using strengthening, stretching, balance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…These results were consistent with the findings of Kankanasamut et al [29], Sartor et al [31], Fayed et al [32], Cerrahoglu et al [33], Jorgetto et al [8], Jiang et al [3], Prokai et al [1], de Oliveira Lima et al [34], and Monterio et al [10]. Kankanasamut et al [29] demonstrated that eight weeks of weight-bearing exercises increases vibration perception.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These results were consistent with the findings of Kankanasamut et al [29], Sartor et al [31], Fayed et al [32], Cerrahoglu et al [33], Jorgetto et al [8], Jiang et al [3], Prokai et al [1], de Oliveira Lima et al [34], and Monterio et al [10]. Kankanasamut et al [29] demonstrated that eight weeks of weight-bearing exercises increases vibration perception.…”
Section: Discussionsupporting
confidence: 87%
“…Prokai et al [1] demonstrated that a 12-week exercise program on the sand, including strengthening, stretching, balance, and walking exercises is a safe and effective method for improving plantar flexion strength, ankle flexibility, and balance, which manifests in better walking performance in patients suffering from diabetic peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Muscle ultrasound has been used to assess muscle mass and muscle quality among young athletes and has been applied to older people recently [ 16 ]. Studies have shown that ultrasound could detect muscle atrophy by measuring CSA, MT, and shear wave velocity (SWV) for foot muscles directly related to foot ulcers and other complications [ 15 , 17 , 18 ]. For large muscle groups of lower extremities, Wang et al [ 19 ] discovered that diabetes duration over ten years and rectus femoris mass index (RFMI) lower than 2.2 cm 2 /m 2 were indicators of DPN with an accuracy of 0.75 (95% CI: 0.72–0.79, p < 0.001).…”
Section: Introductionmentioning
confidence: 99%